Data analytics : paving the way to sustainable urban mobility : proceedings of 4th Conference on Sustainable Urban Mobility (CSUM2018), 24-25 May, Skiathos Island, Greece /: paving the way to sustainable urban mobility : proceedings of 4th Conference on Sustainable Urban Mobility (CSUM2018), 24-25 May, Skiathos Island, Greece. ([2019]) - Unknown
No abstract available